1997
DOI: 10.1103/physrevlett.78.1932
|View full text |Cite
|
Sign up to set email alerts
|

Size, Shape, and Low Energy Electronic Structure of Carbon Nanotubes

Abstract: A theory of the long wavelength low energy electronic structure of graphite-derived nanotubules is presented. The propagating π electrons are described by wrapping a massless two dimensional Dirac Hamiltonian onto a curved surface. The effects of the tubule size, shape and symmetry are included through an effective vector potential which we derive for this model. The rich gap structure for all straight single wall cylindrical tubes is obtained analytically in this theory, and the effects of inhomogeneous shape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
900
2
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,017 publications
(939 citation statements)
references
References 9 publications
36
900
2
1
Order By: Relevance
“…Furthermore, the peak at ∼0.01 eV may be assigned to the curvature-induced pseudogap in the chiral SWNTs. [64][65][66] On a practical note, an important aspect of nanotube chemistry is the level of purity of the starting materials, and most bulk samples are heavily contaminated with non-nanotube impurities. No chemist likes to work with impure starting materials, but this is the usual state of affairs at the present time.…”
Section: Electronic Structure and Chemical Reactivitymentioning
confidence: 99%
“…Furthermore, the peak at ∼0.01 eV may be assigned to the curvature-induced pseudogap in the chiral SWNTs. [64][65][66] On a practical note, an important aspect of nanotube chemistry is the level of purity of the starting materials, and most bulk samples are heavily contaminated with non-nanotube impurities. No chemist likes to work with impure starting materials, but this is the usual state of affairs at the present time.…”
Section: Electronic Structure and Chemical Reactivitymentioning
confidence: 99%
“…Such nanotubes are thus semiconducting whereas the = 0 tubes are nominally metallic. The curvature, however, opens a small gap, [10][11][12][13][14] likely causing the measured gaps of order 10-50 meV in Refs. 18 and 20.…”
Section: ͑1͒mentioning
confidence: 99%
“…8,9 The curved geometry creates a mass term in the Dirac spectrum and thus a band gap even for the nominally metallic tubes. [10][11][12][13][14] This band gap allows for electrostatic confinement of electrons and creation of few-electron QDs, otherwise not possible due to the Klein paradox. 15 Recent experiments have shown that it is indeed possible to confine electrons in single [16][17][18][19] and double QDs ͑DQDs͒ in a CNT by means of electrostatic gates in cleanly grown small band-gap nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…But all these methods create groups at CNT walls, which can act as recombination. Alternativelly, CNTs are suspended in aqueous media by non-covalent interactions using surfactants [7,20,[63][64][65].…”
Section: Cnt Dispersions and Thin Film Formationmentioning
confidence: 99%